State of the Art Review on Hollow Core Slabs - Hussain Ali Yazal; Prof. Dr. Hussam Ali Mohammed (Zien Journals, 2023)
Numerous advancements in concrete technologies have significantly influenced structural systems. This review provides an overview of the existing body of research literature pertaining to hollow-core slabs. The existing body of literature pertaining to the current research can be classified based on prior investigations conducted on the topic of weight reduction of slabs. This paper incorporates the principal findings derived from prior research.
Keywords: hollow core; slabs; reinforcement concrete